2020
DOI: 10.1111/tog.12692
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐implantation genetic testing for aneuploidy: the past, present and future

Abstract: Embryonic aneuploidy is often found in women undergoing assisted reproduction and is a common cause of poor outcomes, particularly in women of advanced maternal age and those with recurrent miscarriage and repetitive implantation failure. The aim of pre-implantation genetic testing for aneuploidy (PGT-A) is to select the most competent embryo for transfer, thus improving reproductive outcome. Initial PGT-A techniques failed to show an improvement in delivery rates and, in some trials, demonstrated inferior out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…31 A recent Cochrane review which included 11 studies on PGT-A using FISH also concluded that the evidence currently available does not support the routine use of PGT-A and highlighted that this method could be harmful. 17 The reasons for the unexpected results from the FISH PGT-A studies are summarized in a recent clinical review, 2 and are generally agreed to be secondary to the limitations of FISH as a chromosome screening technique and the drawbacks associated with cleavage-stage biopsies. FISH enables screening of only up to 9 to 12 chromosomes as defined by the chosen probes; 16 as such, FISH is unable to reliably detect up to 30% of the aneuploidies and segmental abnormalities present in embryos.…”
Section: Initial Pgt-a Methods and Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…31 A recent Cochrane review which included 11 studies on PGT-A using FISH also concluded that the evidence currently available does not support the routine use of PGT-A and highlighted that this method could be harmful. 17 The reasons for the unexpected results from the FISH PGT-A studies are summarized in a recent clinical review, 2 and are generally agreed to be secondary to the limitations of FISH as a chromosome screening technique and the drawbacks associated with cleavage-stage biopsies. FISH enables screening of only up to 9 to 12 chromosomes as defined by the chosen probes; 16 as such, FISH is unable to reliably detect up to 30% of the aneuploidies and segmental abnormalities present in embryos.…”
Section: Initial Pgt-a Methods and Outcomesmentioning
confidence: 99%
“…12 It is possible to biopsy an embryo at three different time points. 2 The choice of timing of the embryo biopsy is also thought to be fundamental in the failure of initial PGT-A studies. 12,15,16 Eight of the nine RCTs included in the metaanalysis of early PGT-A studies used cleavage-stage biopsy, and one used polar body (PB) biopsy.…”
Section: Initial Pgt-a Methods and Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…78 Moreover, this stage embryo facilitates the capability of undertaking preimplantation genetic testing for aneuploidy (PGT-A), in which embryo biopsy from the trophectoderm during the blastocyst stage is favorable. 79 PGT-A facilitates embryo selection by enabling the opportunity to use chromosomally normal embryos, 80 avoiding those which are aneuploid, which may cause fetal abnormality and are accountable for more than half of miscarriages. 81 PGT-A has been shown to increase implantation and pregnancy rates and reduce the risk of miscarriage following single embryo transfer, 82,83 and results in a higher livebirth rate per embryo transfer.…”
Section: Conceptionmentioning
confidence: 99%